The acetylation GLI1 affects arsenical-induced renal fibrosis by mediating the Hedgehog signalling pathway - Pinya Liu; Yating Wang; Peiyu Jin; Qing Zhou; Liang Pei; Shuhua Xi (Ecotoxicology and Environmental Safety)
Arsenic exposure by drinking water is a key challenge in the field of public health worldwide. Research has found a connection between arsenic exposure and renal fibrosis, yet the mechanisms behind this are still unclear. In this study, rats were exposed to 50 mg/L NaAsO2 or 200 mg/L dimethylarsinic acid (DMA) via drinking water for 12 weeks, and HK-2 cells were treated with 1 μM NaAsO2 for 4 weeks. The results showed that the renal tubular structure was destroyed, renal function was impaired, and fibrosis occurred in renal tissue in arsenic-exposed F344 rats. Arsenic-treated HK-2 cells presented hydroxyproline levels elevating and fibrosis-related proteins expression increasing. In addition, the levels of Hedgehog signaling pathway-related factors SMO, SHH, GLI1, GLI2 were increased and SUFU was decreased in kidneys of arsenic-treated rats and HK-2 cells, indicating that the Hedgehog signaling pathway was triggered. The fibrosis level was reduced in arsenic treated HK-2 cells after interference with the Hedgehog pathway inhibitor. The activity of GLI1, an important factor in the Hedgehog signaling pathway, is regulated by acetylation modifications. Levels of GLI1 acetylation were reduced in arsenic treated HK-2 cells11 Inhibition of deacetylation reduces fibrosis in arsenic-treated HK-2 cells.. In conclusion, the Hedgehog signaling pathway is vital in arsenic-triggered renal fibrogenesis.